Ian Logan, Reading Anselm´s “Proslogion": The history of Anselm´s argument and its significance today, Ashgate, Farnham, 2009; 220 p. ISBN 978-0-7546-6123-8. - Peretó Rivas, Rubén (2011)
Fil: Peretó Rivas, Rubén.